RETRACTED: Pengaruh Kinerja Mengajar Guru, Keterlibatan Orang Tua, Aktualisasi Diri Terhadap Motivasi Berprestasi - Junianto, Dwi (Jurnal Pendidikan Teknologi dan Kejuruan, 2015)
RETRACTEDFollowing a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Teknologi dan Kejuruan entitled “Pengaruh Kinerja Mengajar Guru, Keterlibatan Orang Tua, Aktualisasi Diri terhadap Motivasi Berprestasi”, Vol 22, No 3, pp. 262-273, May 2015DOI: http://dx.doi.org/10.21831/jptk.v22i3.6834This paper has been found to be in violation of the Jurnal Pendidikan Teknologi dan Kejuruan Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published in Jurnal Pendidikan Vokasi ISSN: 2476-9401, Vol. 3, No. 3, 2013 pp 307-318DOI: http://dx.doi.org/10.21831/jpv.v3i3.1845The document and its content has been removed from Jurnal Pendidikan Teknologi dan Kejuruan, and reasonable effort should be made to remove all references to this article.